How general practitioners manage mental illness in culturally and linguistically diverse patients: An exploratory study - Harding, S.; Schattner, P.; Brijnath, Bianca (The Royal Australian College of General Practitioners, 2015)
Background: General practitioners (GPs) see a range of mental illnesses and a diversity of patients, including patients from culturally and linguistically diverse (CALD) backgrounds. The aim of this study was to understand the barriers and facilitators GPs encounter when managing mental illness in CALD patients. Methods: Semi-structured interviews with 10 Melbourne GPs were undertaken between May and July 2013. Data were analysed thematically. Results: GP barriers included difficulties in recognising initial symptoms, communicating the diagnosis and using interpreter services. Facilitators included cultural concordance between the GP and patient, practice-based initiatives targeting CALD patients, and areas of further education for GPs and CALD patients. Discussion: Cultural concordance between GPs and CALD patients is likely to be effective in facilitating management of mental illness. Further research is needed on interpreter use and scaling up practice-based initiatives to improve service delivery. At a population level, GPs thought it necessary to improve mental health literacy in CALD communities.